Cerebrospinal fluid AFB smear in adults with tuberculous meningitis: A systematic review and diagnostic test accuracy meta-analysis. (July 2022) - Stadelman, Anna M.; Ssebambulidde, Kenneth; Buller, Alexandria; Tugume, Lillian; Yuquimpo, Kyle; Bakker, Caitlin J.; Boulware, David R.; Bahr, Nathan C.
Abstract: Background: Cerebrospinal fluid (CSF) Ziehl–Neelsen acid-fast bacilli (AFB) smear is a rapid, cheap, widely available test for tuberculous meningitis (TBM). Yet, reported test sensitivity is highly variable. We performed a systematic review and meta-analysis for CSF AFB smear vs. other mycobacterial tests to diagnose TBM. Methods: We searched MEDLINE and Embase for studies reporting sensitivity and specificity of AFB smear against mycobacterial tests (reference standard) in adults (≥15 years) with suspected TBM. We used the QUADAS-2 tool to assess risk of bias. We estimated pooled sensitivity and specificity of AFB smear versus the reference standard using random-effects bivariate modeling. We used the I 2 statistic to assess heterogeneity between studies. Results: Of 981 articles identified, 11 were eligible for inclusion with a total of 1713 participants. Seven studies were from high-TB burden settings and 4 from low-TB burden settings. The pooled sensitivity and specificity of CSF AFB smear were 8% (95%CI 3–21) and 100% (95%CI 90–100), with substantial heterogeneity in diagnostic performance ( I 2 >95% for both) and reference standards. Conclusion: CSF AFB smear has poor sensitivity in most settings. If other more sensitive tests are available, those should be used preferentially rather than CSF AFB smear.